Implementation of smart governance in the smart city program at the communication and informatics office in Sukabumi - Faris Nandi Prasetiyo; Yana Fajar Basori; Dian Purwanti (Universitas Merdeka Malang, 2024)
Sukabumi City in West Java Province, as a city that uses the Smart City concept, continues to be committed to the Smart City program based on Sukabumi Mayor Decree Number 73 concerning the Establishment of the Smart City Action Plan Activity Compilation Team in Sukabumi City. The aim is to establish Smart City development planning guidelines based on Smart Governance, Smart Economy, Smart People, Smart Mobility, Smart Living, and Smart Environment. The Smart City concept is carried out to overcome complex problems in urban life. This research aims to discover the Application of Smart Governance in Developing the Smart City Concept at the Communication and Informatics Office of Sukabumi City. The research method was carried out using descriptive qualitative methods. Snowball sampling was used to determine informants, and data collection techniques included observation, documentation, interviews, and audio-visual materials. The results of this study indicate that the implementation of smart governance in the innovative city program at the communication and informatics office of Sukabumi has been realized. Still, there are several inhibiting factors, such as complaints from users of online complaint service applications that experience network and application problems.